Heterogeneous activation of persulfate by Mg doped Ni(OH)2 for efficient degradation of phenol. (January 2022) - Zhu, Fang; Zhou, Siyi; Sun, Mengying; Ma, Jianfeng; Zhang, Wei; Li, Kunjie; Cheng, Hao; Komarneni, Sridhar
Abstract: Mg doped Ni(OH)2 was synthesized and investigated as an efficient material to activate persulfate (PS) for phenol degradation. The property of the Ni(OH)2 material was enhanced by Mg doping as the removal efficiency of phenol was increased from 74.82 % in Ni(OH)2 /PS system to 89.53 % in Mg-doped Ni(OH)2 /PS system within 20 min. Such a high removal efficiency revealed that doping Mg into Ni(OH)2 brings about more defects (oxygen vacancies), which facilitated the formation of more active species in the degradation process. The removal efficiencies of phenol increased with the increase of the initial pH from 3 to 11. The influences of Cl −, NO3 − and HCO3 − on the stability of the system were also studied and the results showed that removal rates of all systems in the presence of these different inorganic anions could reached about 90 % within 20 min. Based on the electron spin resonance (ESR) experiments, 1 O2, O2 ·-, ·OH and SO4 − were identified as the active species in Mg-doped Ni(OH)2 /PS system for phenol degradation and a degradation mechanism was proposed for this system. In addition, the as-prepared material retained its activation performance even after 3 repeated cycles. Highlights: Potassium persulfate was activated by Mg doped Ni(OH)2 to degrade phenol. The removal efficiency of phenol reached 89.53 % within 20 min. Doping Mg into Ni(OH)2 leads to many defects (oxygen vacancies). 1 O2, O2 · -, ·OH and ·SO4 − were the major active species for phenol degradation.